Odpowiedzi

2009-11-17T20:46:44+01:00
12-2(x-1)²=4(x-2)-(x-3)(2x-5)
12-2(x²-2x+1)=4x-8-(2x²-5x-6x+15)
12-2x²+4x-2=4x-8-2x²+5x+6x-15
10-2x²+4x=15x-23-2x²
2x²-2x²+4x-15x= -33
-11x = -33
x = 3

(x-3)(x+2)(x+2)=(x-1)³+6
(x-3)(x+2)² = x³ - 3x² + 3x - 1 + 6
(x-3)(x²+4x+4) = x³- 3x² + 3x +5
x³ + 4x² + 4x - 3x² - 12x - 12 = x³- 3x² + 3x + 5
4x² - 3x ² + 3x²-3x - 12x = 12 + 5
4x² - 15 x = 17 (Tu nie jestem pewien , sprawdz !)


2x²+(x+5)²-2(x+7)²=2(3x-72,5)+(x-6)²
2x² + (x² + 10x + 25) -2(x²+14x + 49) = 2(3x-72,5)+(x²-12x + 36)
2x² + x² + 10x + 25 -2x² - 28x - 98 = 6x - 145 + x² - 12x + 36
10x + 25 - 28x - 98 = 6x - 145 - 12x + 36
10x - 28x - 6x + 12x = 36-145-25
-12x = -134
x ≈ 11,2
2 1 2
Najlepsza Odpowiedź!
2009-11-17T20:47:12+01:00
A) 12-2(x-1)²=4(x-2)-(x-3)(2x-5)
12-2(x²-2x+1)=4x-8-(2x²-5x-6x+15)
12-2x²+4x-2 =4x-8-2x²+11x-15
10-2x²+4x =-2x²+15x-23
-2x²+4x+2x²-15x =-33
4x-15x =-33
-11x =-33
x=3
b) (x-3)(x+2)(x+2)=(x-1)³+6
(x-3)(x²+4x+4)=(x³-3x²+3x-1)+6
x³+4x²+4x-3x²-12x-12=(x³-3x²+3x-1)+6
x³+x²-8x-x³+3x²-3x=5+12
4x²+11x=17


c)2x²+(x+5)²-2(x+7)²=2(3x-72,5)+(x-6)²
2x²+x²+10x+25-2(x²+14x+49)=6x-145+x²-12x+36
2x²+x²+10x-2x²-28x-6x-x²+12x=-145+36-25+98
-12x=-36
x=3
1 5 1
  • Użytkownik Zadane
2009-11-17T21:01:34+01:00
A) x=3
b) x=13/7
c) x=3

co do odpowiedzi wyzej:
w zadaniu B) jest (x+2)(x-2) co jest rowne x^2-4 a nie (x+2)^2